Effect of alternating canal and marginal groundwater irrigation on banana yield, water use efficiency, and soil salinity under furrow plantation - Gul, N.; Salam, H. A.; Ashraf, Muhammad; Semiromi, M. T. (Elsevier, 2025)
Banana is one of the most important cash crops in Sindh, Pakistan; however, its production is increasingly compromised due to declining freshwater availability. Currently, banana is cultivated using conventional flat basin irrigation, which results in low water use efficiency (WUE). Groundwater in the region is predominantly marginal to saline in quality but could potentially supplement limited freshwater resources. Therefore, it is essential to evaluate the conjunctive use of marginal-quality groundwater and canal water to address freshwater shortages without compromising crop yields. In this study, the Dwarf Cavendish banana variety (locally known as Basrai) was cultivated over a four-year period (October 2015–June 2019) on furrows (0.90 m furrow width, 1.20 m bed width, and 0.23 m bed height). Alternate irrigation using canal and marginal groundwater was applied at three levels of available soil moisture depletion (ASMD): 50 %, 40 %, and 30 %. Traditional farmer irrigation practices were also monitored for comparison. At ASMD levels of 50 %, 40 %, and 30 %, annual water applications were 1228 mm, 1403 mm, and 1592 mm, respectively. In contrast, farmers applied 2866 mm of water annually. Irrigation at 50 % ASMD resulted in 12–23 % higher yield and 23–41 % higher WUE compared to 30 % and 40 % ASMD treatments. Compared to the 50 % ASMD treatment, farmer practices produced 24 % lower yield and 67 % lower WUE. Importantly, soil salinity remained within acceptable threshold limits across all treatments. These results suggest that banana can be successfully cultivated on furrows using alternate irrigation with canal and marginal groundwater at 50 % ASMD. This strategy offers substantial water savings while improving yield and WUE, making it a viable and sustainable solution for banana production in water-scarce regions.